Role of organic manures on soil carbon stocks and soil enzyme activities in intensively managed ginger production systems - C Nichita; Raghavendra S; B Champa; Ganapathi G; Sudarshan V; Nandita S; Ravikumar D; M Nagaraja (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Application of organic manures, along with fertilizers, is important to maintain soil fertility to achieve higher productivity. In reality, the farmers apply organic manures and fertilizers in different proportions and quantities depending on their availability and purchasing power of farmers. Organic manures also help to enhance soil carbon stocks and soil biological activities. Hence, this study aimed to assess the role of organic manures on soil carbon stocks and soil enzymes in intensively managed ginger production systems.Method: Farmers’ fields based study was conducted in Shivamogga district coming under Hilly Zone of Karnataka, India. The information on use of organic manures and fertilizers for ginger production were collected from 60 growers and they were grouped into three categories using the K-factorization statistical tool. Soil samples were collected after crop harvest and analysed for soil carbon stocks and soil enzyme activities. The mean values of 3 categories of farmers were compared using suitable statistical tools.Results: Added organic manure and the soil organic carbon (SOC) varied significantly among high and low organic manure applications. Incremental variations were observed in the order of Category 3 > Category 2 > Category 1 ginger fields. Enzyme activities were found higher in fields applied with high organic manures. Both soil carbon stocks and soil enzyme activities exhibited strong and positive correlations with organic manures.Conclusion: The study revealed that application of organic manures in intensively managed ginger production systems helps to enhance soil carbon stocks and maintain soil biological activities.